KEBIJAKAN PEMERINTAH TENTANG PENGELOLAAN BADAN USAHA MILIK DESA ABBOKONGANG KECAMATAN KULO KABUPATEN SIDENRENG RAPPANG - Zainal Abidin Kahar; Sahar Sahar; Ahmad Yasin; Andi Sinrang; Muhammad Ikbal (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2022)
The purpose of this study was to find out how the government policy regarding the management of business entities owned by the village of Abbokongang, Kulo district, Sidenreng Rappang district and to find out how the management of enterprises owned by the village of Abbokongan, Kulo district, Sidenreng Rappang district. The population in all heads of families in Abbokongan Village A total of 508 family heads from the total population of 1864 people, while the sampling used was a purposive sampling technique where the sampling was taken with the consideration of the researcher, that of the 51 people selected they were people who knew about management. BUMDes. This type of research is quantitative with a quantitative descriptive type approach that aims to explain systematically and professionally. Data collection techniques used are observation, questionnaires, and literature study. The data analysis technique used is descriptive statistical analysis with the help of SPSS. The results obtained through questionnaires from policy implementation. The accumulation of the average percentage results of the 8 question items on the policy implementation indicators above, then the average percentage result is 73.3%, it can be concluded that this indicator is in the category